Intervensi Gizi Meningkatkan Praktik Pemberian Makan Anak Stunting - Erna Julianti; Elni Elni; Restu Amalia Azmy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify differences in the average feeding practices of stunted clowns in the intervention and control groups. Quantitative Research Method with a quasi-experiment post-test only control group design. The analysis in this study used the Independent T-Test. The study results showed that the average feeding practice for stunted clowns in the intervention group was higher at 112.32 compared to the intermediate feeding practice for stunted clowns in the control group of 77.71. The analysis using the independent T-test showed a significant difference between the average feeding practices of stunted clowns in the intervention group and the control group, with a p-value of 0.0001. The conclusion is that implementing nutritional interventions can improve the practice of feeding stunted toddler children. Keywords: Nutritional Intervention, Feeding, Stunting